Surviving against the odds: outcomes of emergency resuscitative thoracotomies at an Australian level 1 trauma centre - Hayler, Raymond R.; Singh, Arushi; Selvendran, Selwyn T.; Langcake, Mary E. (International Surgery Journal, 2022)
Background: Emergency resuscitative thoracotomy (ERT) is performed in thoracic trauma patients who present in extremis. Newer studies outside North America report higher survival rates, however literature from Australia is limited. This study reviews 12 years of ERT outcomes from an Australian level 1 trauma centre and whether trauma triage mechanisms may impact survival rates Methods: A retrospective observational study using data from the trauma registry at St. George hospital Sydney for all who underwent an ERT between 2009 and 2021, supplemented with information from medical records. Parameters examined included demographics, injury profile, ERT details and outcomes. Data was then analysed by descriptive statistics Results: The 29 ERTs were performed of which 25 were male (85%) and 4 were female (14%). Mean age was 40 and mean injury severity score (ISS) was 32. Overall, 13 patients survived after ERT (45%), with 10 patients surviving admission post ERT for penetrating injuries (53%), compared to 3 surviving admissions for blunt injuries (27%). The 82% of ERTs were performed in the operating theatre (OT), with survival rates the highest when ERT was performed in OT by the cardiothoracic surgical team Conclusions: In this study, ERT conferred good outcome with survival in almost half of patients. More studies are required to establish whether triage mechanisms which facilitate early transfer to OT confer higher survival in ERT patients.